Penggunaan Media Kakruf untuk Meningkatkan Literasi pada Anak Kelas II di SDK Masu - Prodensiana Eno; Konstantinus Dua Dhiu; Andi Nafsia; Elisabeth Tantriana Ngura (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to improve the process of implementing initial reading learning through Kakruf games can improve the results of students' reading skills. The subject of this study is 2nd grade students of SDK Masu which totals 24 students. This type of research is PTK (Classroom Action Research). The data collection technique uses tests and observations. The data collection instruments are student learning outcome tests and observation sheets. The data analysis technique used is quantitative descriptive data analysis. The learning process of cycle I teachers apply letter card games. Cycle II teachers apply letter card games and group discussions. The results of the first cycle of students' reading skills increased from the results of pre-action with an average score of 60.83% increased to 71.25%, and students who achieved KKM by 75%. In cycle II, the average score increased to 80.83% and students who had achieved KKM were 100%. The results of the study show that the Kakruf game can improve students' beginner reading skills.